Pengaruh Jarak dan Kemiringan Plate Settler pada Reaktor Grease Trap terhadap Penurunan Kadar Lemak dan Minyak Limbah Cair Pelayanan Makanan - Yosephina Ardiani Septiati; Annisa Pratiwi P; Siti Rochmah; D Dwinovita (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2022)
Liquid oil waste water cause oxygen solubility and damage aquatic life. The purpose of the study: knowing the effect of distance and slope between settler plates on grease trap reactors on the elimination of oil and wastewater fats. The research method used field experiments, food service wastewater samples of as much as 250 liters with fat and oil content of 92 mg/l-152 mg/l with random sampling techniques consist of 3 treatments with 6 repetitions, namely treatment 1 (distance 1 cm-slope 500, 600, 700), treatment 2 (distance 2 cm-slope 500, 600, 700), treatment 3 (distance 3 cm-slope 500, 600, 700). There is a significant influence between distance and slope to decreased levels of oil and liquid waste fats (p-value<0.001). There is a jointly significant influence between distance and slope against the decrease in oil levels and liquid limbar fat, with a distance of 1 cm and a slope of 600 providing the largest average decrease in oil and fat content of 93.6 mg/l. Liquid waste advice PT X should be processed to prevent water pollution.